As-cast ternary polymer solar cells based on a nonfullerene acceptor and its fluorinated counterpart showing improved efficiency and good thickness tolerance. Issue 16 (2nd April 2019) - Pan, Feilong; Zhang, Lianjie; Jiang, Haiying; Yuan, Dong; Nian, Yaowen; Cao, Yong; Chen, Junwu
Abstract : PBDB-T-SF : IDIC : ID4F ternary blend films show 11.52% power conversion efficiency, higher than 9.39% and 10.35% for the corresponding binary devices. Abstract : A ternary blend by introducing a third component into a binary blend for a polymer solar cell (PSC) is a promising strategy because the light absorption, morphology, and carrier transport of the active layer as well as energy level alignment of the donor and the acceptor may be optimized. In this work, a nonfullerene acceptor IDIC and its fluorinated acceptor ID4F were selected to combine with a PBDB-T-SF donor in the construction of ternary blends. The as-cast ternary PSCs can achieve a higher power conversion efficiency (PCE) of 11.52% than the IDIC (9.39%) and ID4F (10.35%) based binary PSCs. The enhanced PCEs of the ternary PSCs are based on the higher electron mobility, more balanced charge transport, and optimized phase separation. Moreover, the ternary PSCs also show good thickness tolerance with a PCE > 10% from 85 to 250 nm and better shelf stability than the two binary PSCs. Our results indicate that mixing a nonfullerene acceptor and its fluorinated counterpart with the closest structural similarity to form a ternary blend is a valuable strategy to improve photovoltaic performances.